2009
DOI: 10.4000/quaternaire.5244
|View full text |Cite
|
Sign up to set email alerts
|

Nouvelles données sur le site majeur d’Écalgrain : datations radiométriques et occupations humaines de la Pointe de la Hague (Cotentin, Normandie)

Abstract: de plages perchées reposant sur deux plates-formes d'abrasion marine : la plage inférieure de 4 à 6 m NGF et la plage supérieure entre 12 et 18 m. Ces paléoplages sont recouvertes par des heads périglaciaires (dépôts de gélifluxion) et par des loess. La plage inférieure date le plus souvent de l'Eemien et ses dépôts de couverture du Weichselien. La plage supérieure correspond à l'optimum du stade isotopique 7. Cependant, dans la baie d'Ecalgrain, l'âge de la basse plage est discuté. Les formations de couvertur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…The northwest coast of France, from Britany to the Straits of Dover, is characterised by the occurrence of a staircase of polygenic coastal platforms that were correlated with Pleistocene interglacial periods. These platforms are intermittently covered by a variety of coastal (mainly raised beaches) and periglacial deposits (heads and loess) that have been studied for more than a century (Barrois, 1877(Barrois, , 1882Bigot, 1885Bigot, , 1930Guilcher, 1948;Pellerin and Dupeuble, 1979;Lautridou et al, 1999;Regnauld et al, 2003;Coutard et al, 2005Coutard et al, , 2006Cliquet et al, 2009;Pedoja et al, 2018). The absence of wellpreserved fossiliferous remains in most of these sites gave rise to an extensive discussion about their chronostratigraphy, and the age was generally established based on the altitude of the beach deposits relative to other sites.…”
Section: English Channel: Northwest Francementioning
confidence: 99%
See 2 more Smart Citations
“…The northwest coast of France, from Britany to the Straits of Dover, is characterised by the occurrence of a staircase of polygenic coastal platforms that were correlated with Pleistocene interglacial periods. These platforms are intermittently covered by a variety of coastal (mainly raised beaches) and periglacial deposits (heads and loess) that have been studied for more than a century (Barrois, 1877(Barrois, , 1882Bigot, 1885Bigot, , 1930Guilcher, 1948;Pellerin and Dupeuble, 1979;Lautridou et al, 1999;Regnauld et al, 2003;Coutard et al, 2005Coutard et al, , 2006Cliquet et al, 2009;Pedoja et al, 2018). The absence of wellpreserved fossiliferous remains in most of these sites gave rise to an extensive discussion about their chronostratigraphy, and the age was generally established based on the altitude of the beach deposits relative to other sites.…”
Section: English Channel: Northwest Francementioning
confidence: 99%
“…The discovery and excavation of Palaeolithic sites along the coast and the progressive application of thermoluminescence (TL), optically stimulated luminescence (OSL) and electro spin resonance (ESR) geochronology (e.g., Balescu et al, 1991;Balescu and Lamothe, 1992;Loyer et al, 1995;Folz, 2000;Coutard et al, 2006;Cliquet et al, 2003Cliquet et al, , 2009Monier et al, 2011) boosted the understanding of the coastal sequences and helped to better constraint the distribution of the LIG deposits. Loyer et al, (1995) suggested that up to four different interglacials were preserved in the same coastal platform in Saint-Brieuc Bay (Britany) based on palaeoenvironmental data and TL dating of loess deposits, later further supported by ESR dating of Palaeolithic sites (Bahain et al, 2012).…”
Section: English Channel: Northwest Francementioning
confidence: 99%
See 1 more Smart Citation
“…Les assemblages lithiques associés à ces niveaux d'occupation se rapportent à la phase ancienne du Paléolithique moyen, sauf peut-être pour le site de la Saline qui pourrait être plus ancien et se rapporter à l'Acheuléen (?) (Cliquet et al, 2003b(Cliquet et al, , 2009d. Parmi les découvertes récentes figure le site de Digulleville à Jardeheu.…”
Section: -Dans Le Nord-cotentinunclassified
“…En Normandie armoricaine, les sites de la fin du Pléistocène moyen sont plus nombreux et souvent associés aux formations sus-jacentes à la plateforme de +12 / +15 m NGF (plages, sables dunaires) du SIM 7 et aux niveaux d'habitat interstratifiés dans les heads du SIM 6. Ce sont fréquemment des accidents topographiques mis à profit par les hommes du Paléolithique pour structurer leur habitat qui ont favorisé la conservation des niveaux d'occupation : pied d'écueil à Digulleville, couloir entaillé dans le granite à Fermanville / Port-Pignot, crique à Saint-Germain-des-Vaux / Gélétan… Cependant quelques sites se trouvent incorporés aux plateformes de +5 / +8 m NGF ; ils correspondent soit à des implantations du SIM 7 en phase régressive, comme à Ecalgrain daté de 190 ± 19 ka (Cliquet et al, 2009d), soit aux occupations dans une cuvette ouverte dans le platier granitique de Gouberville, vers +5 m NGF, datées par TL sur silex chauffés entre 187 ± 26 et 128 ± 20 ka. Ces industries se rapportent à la phase ancienne du Paléolithique moyen.…”
Section: Conclusion Partielle : Mis 7 Et 6 Dans Le Contentinunclassified